Risk and Asset Integrated Management with Risk-Based Inspection Technique in Oil, Gas, and Petrochemical Industries - Amir BARKHORDARI; Yazdan MAHMOUDIAN; Fateme YOUSEFI; Peyman ZAREI; Behnam MORADI (Shahid Sadoughi University of Medical Sciences, 2020)
Abstract Introduction: To prevent accidents and minimize the risk of unexpected disasters in the oil, gas, and petrochemical industries, an inspection of equipment in terms of mechanical integrity and safe and consistent service providing are of utmost importance. The purpose of this study is integrated risk and asset management by implementing risk-based inspection techniques in the oil, gas, and petrochemical industries. Methods: Firstly, this systematic review study identified a list of keywords based on RBI and then exclusively on the internal and external databases of Science Direct, Pub med, Google Squalor, SDI, Google Searcher, and Scopus without a time limit. Afterward, keywords, including risk management, probability of failure, asset integrated management, risk-based inspection, consequences of failure, and corrosion management, were searched. Result: A review of various studies showed that the risk-based inspection approach provided the necessary platform for upgrading and formulating new inspection, repair, maintenance, equipment risk management systems and asset integration in the oil, gas, and petrochemical industries and played a significant role in reducing the risk levels to its acceptable limits. Conclusion: By analyzing the results of studies, it was found that using this method will lead to the effective implementation of risk management, reliability, and corrosion management in oil, gas, and petrochemical industries. In fact, the system intended to provide process safety, increase risk perception of damage in line with the respective risk management, and ensure the integrity of the assets in operational units.